Technological innovations in augmented reality systems for art performances - Syromiatnykova, D.; Suprun, O. (ХНЕУ, 2026)
Recent research focuses on enhancing the robustness of Simultaneous Localization and Mapping (SLAM) systems in complex performance scenarios.
Keywords: innovations; art performances